2018
DOI: 10.1016/j.bbadis.2017.06.028
|View full text |Cite
|
Sign up to set email alerts
|

The role of macrophages in the development of biliary injury in a lipopolysaccharide-aggravated hepatic ischaemia-reperfusion model

Abstract: Depletion of hepatic macrophages did not prevent development of biliary injury following LPS or LPS-enhanced IRI. Cholangiocyte activation rather than macrophage activation may underlie this injury. This article is part of a Special Issue entitled: Cholangiocytes in Health and Diseaseedited by Jesus Banales, Marco Marzioni, Nicholas LaRusso and Peter Jansen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…LPS-induced hepatic injury is the pathological basis of varied hepatic diseases. However, the injury is considered indirect and induced by the production of pro-inflammatory cytokines from activated Kupffer cells[ 12 ]. In this current study, we found that serum levels of AST and ALT were visibly high in both β-arrestin 2 KO and WT mice treated with LPS for 4 h (Figure 1A and B).…”
Section: Discussionmentioning
confidence: 99%
“…LPS-induced hepatic injury is the pathological basis of varied hepatic diseases. However, the injury is considered indirect and induced by the production of pro-inflammatory cytokines from activated Kupffer cells[ 12 ]. In this current study, we found that serum levels of AST and ALT were visibly high in both β-arrestin 2 KO and WT mice treated with LPS for 4 h (Figure 1A and B).…”
Section: Discussionmentioning
confidence: 99%
“…To directly explore the role of periphery macrophages in the pathogenesis of PD, we depleted the macrophages by intraperitoneally injecting clodronate liposomes, which has been used in several stress and LPS studies (Kotter et al, 2001 ; Zhu et al, 2015 ; Reiling et al, 2018 ). We used the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) induced mouse model of PD to assess the activation status of macrophages in peripheral immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, when the ischemic myocardium recovers blood flow, due to the production of oxygen free radicals, the damaged cardiomyocytes release endogenous risk signals to recruit inflammatory cells to nest, start/amplify local inflammatory response, resulting in secondary damage of cardiomyocytes [51] . Inhibition of excessive inflammatory response can reduce the area of myocardial infarction and improve cardiac function [52] , [53] . It is confirmed that the local changes of I/R injury are mainly inflammatory reaction with neutrophil and monocyte infiltration [11] , [51] .…”
Section: Discussionmentioning
confidence: 99%